OPTI-HEP-D: a protocol for an intervention study comprising screening and linkage to care of people living with hepatitis D in Catalonia - Maria Buti; Dúnia Pérez del Campo; Gema Fernández; Maria Antònia Llopis; Laura Calatayud; Adriana Palom; Ariadna Rando-Segura; Alicia Sellés-Sánchez; Saray Mormeneo Bayo; Maria Mar Olga Perez Moreno; David Tabernero; Josefina Ayats; et al. (BMJ Open)
Introduction Hepatitis B virus (HBV) affects 296 million people globally, causing 780 000 annual deaths. It has been estimated that 12–43 million individuals are co-infected with hepatitis D virus (HDV). In Spain, the prevalence of HBsAg in adults is 0.22%, with an anti-HDV prevalence of 7.7%, although not extensively documented since many HBsAg-positive cases are not tested for anti-HDV. The primary objective of this project is to optimise hepatitis D care by implementing a screening programme for anti-HDV in all HBsAg-positive individuals over a 1 year period in Catalonia. Secondary objectives include evaluating hepatitis D prevalence, establishing a digital registry for all anti-HDV positive cases, testing them for HDV-RNA in a centralised laboratory and offering linkage to care.Methods and analysis This prospective study will be performed in seven hospital centres in Catalonia, which attend to more than 95% of the adult population. Approximately, 9290 HBsAg-positive individuals are expected to be screened for anti-HDV in 1 year. All anti-HDV positive samples will be sent to a centralised laboratory for HDV-RNA quantification. All individuals testing positive for anti-HDV will be registered on an electronic platform and linked to care. The registry will collect data on demographics, infection stage, risk factors, disease awareness and previous diagnoses. No additional interventions will be conducted for those with adequate follow-up.Ethics and dissemination The Vall d’Hebron Hospital Ethics Committee (PR(AG)628/2023) and the Spanish Agency of Medicines and Medical Devices approved this study. These findings will be disseminated through peer-reviewed publications and conference presentations.Trial registration study Grant number: IN-ES-980–7058.